Christian brother in a special Benediction service - Santos, Rufino J. Cardinal (Animo Repository, 1961)
His Eminence Rufino J. Cardinal Santos became an adopted Christian Brother in a special Benediction service held at the St. Joseph's Chapel on this date. The event coincided with the Golden Jubilee celebrations of the College this year. The Letter of Affiliation was presented by Bro. Hyacinth Gabriel, FSC, Auxiliary Visitor of the Christian Brothers in the Philippines.